2017
DOI: 10.1007/s00259-017-3887-x
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary results on response assessment using 68Ga-HBED-CC-PSMA PET/CT in patients with metastatic prostate cancer undergoing docetaxel chemotherapy

Abstract: Our preliminary results suggest that Ga-PSMA PET might be a promising method for treatment response assessment in mCSPC and mCRPC. The data indicate that for different metastatic sites, the performance ofGa-PSMA PET in response assessment might be superior to that of the conventional CT approach and could help differentiate between progressive disease and treatment response. Because of the limited number of patients, the differences revealed in our study were not statistically significant. Thus larger and pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
100
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 117 publications
(103 citation statements)
references
References 33 publications
2
100
0
1
Order By: Relevance
“…3,4 In this regard, PSMA 11-PET/CT (MRI), which combines morphological with functional imaging, has shown promising results concerning response assessment in two recently published studies. 12,13 This is in agreement with preclinical studies, which have demonstrated that PSMA uptake in the tumor reliably reflects the number of living tumor cells. 16 Another study evaluating the role of PSMA dynamics in men undergoing treatment for advanced PC showed that the PSMA expression in circulating tumor cells shows promising results as a dynamic marker for therapy response.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…3,4 In this regard, PSMA 11-PET/CT (MRI), which combines morphological with functional imaging, has shown promising results concerning response assessment in two recently published studies. 12,13 This is in agreement with preclinical studies, which have demonstrated that PSMA uptake in the tumor reliably reflects the number of living tumor cells. 16 Another study evaluating the role of PSMA dynamics in men undergoing treatment for advanced PC showed that the PSMA expression in circulating tumor cells shows promising results as a dynamic marker for therapy response.…”
Section: Discussionsupporting
confidence: 89%
“…The PET parameters SUVmean and PSMA TTV have been used and investigated for response assessment in this setting in studies before. 12,13 To the best of our knowledge, this is the first study additionally providing response data for the PET parameters SUVmax, SUVpeak, and TTV in a cohort treated with systemic therapies other than radioligand therapy. Within our whole cohort of 67 systemic therapies for mCRPC patients, we could show that all the observed PSMA 11-PET parameter, as well as RECIST criteria, showed significant associations with BR (dTTV P = .003, dSUVmean P = .003, dSUVmax P = .011, dSUVpeak P < 0,001, which is another argument for using hybrid imaging techniques combining morphological and functional imaging information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, 177 Lu-PSMA RLT has been introduced only recently and the number of patients with an excellent response is limited. Second, because of the lack of an established system to evaluate response on PSMA PET, we adopted PERCIST 1.0, as previously described (8). The validation of PERCIST for non-18 F-FDG application is still under discussion.…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical response was defined as a PSA decline of at least 30%, 50%, and 90% during initial and rechallenge treatment. For radiographic response, 68 Ga-PSMA-11 PET/CT findings were assessed as described recently (8). Clinical response was assessed by Eastern Cooperative Oncology Group performance status and changes in bone pain from the Brief Pain Inventory.…”
Section: Methodsmentioning
confidence: 99%